Análisis de Modelos Computacionales para Sistemas Embebidos - Osio, Jorge R. (2006)
After a short summary about the principles of Hardware/Software Codesign (HSCo) for embedded systems, this paper considers an analysis of the software resources mostly used by the academic community with special emphasis on one of them (PeaCE). An example shows how to specify a system considering the computer models, specially the Data Flow formal model. The required characteristics are defined, with the periodic update of parameters and dynamic behavior of functional blocks. An application from the communication area is presented to show the advantages of the chosen system of HSCo. If can generate an efficient code (C and VHDL) very useful to be implemented on generic processors or FPGA, for rapid prototyping.